2018
DOI: 10.1073/pnas.1720476115
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-ET reveals the macromolecular reorganization of S. pombe mitotic chromosomes in vivo

Abstract: Chromosomes condense during mitosis in most eukaryotes. This transformation involves rearrangements at the nucleosome level and has consequences for transcription. Here, we use cryo-electron tomography (cryo-ET) to determine the 3D arrangement of nuclear macromolecular complexes, including nucleosomes, in frozenhydrated Schizosaccharomyces pombe cells. Using 3D classification analysis, we did not find evidence that nucleosomes resembling the crystal structure are abundant. This observation and those from other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 70 publications
(84 reference statements)
4
85
2
Order By: Relevance
“…Furthermore, the G0 nucleoplasm appears even denser than the G1 nucleoplasm ( Figure 2, C and D). In both cell types, we did not find any evidence of cryo-ET densities that resemble highly compacted chromatin masses, which are present in the nuclear lysates of both budding and fission yeasts 11,27 .…”
Section: Both G1 and G0 Cells Have Crowded Nucleicontrasting
confidence: 61%
See 3 more Smart Citations
“…Furthermore, the G0 nucleoplasm appears even denser than the G1 nucleoplasm ( Figure 2, C and D). In both cell types, we did not find any evidence of cryo-ET densities that resemble highly compacted chromatin masses, which are present in the nuclear lysates of both budding and fission yeasts 11,27 .…”
Section: Both G1 and G0 Cells Have Crowded Nucleicontrasting
confidence: 61%
“…We recently used electron cryotomography (cryo-ET) to study S. pombe mitotic chromosome condensation. Our cryotomograms revealed that chromatin compaction as visualized by cryo-ET is less conspicuous than what is seen by fluorescence microscopy 11 . There is no well-defined boundary between condensed chromatin and nucleoplasm because the nucleus is crowded with macromolecular complexes.…”
Section: Introductioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The question therefore remains whether the observed structures are also prevalent in vivo. Recently, the Gan group applied cryo-ET of macromolecular structures in their native cellular environment to mitotic chromatin of Schizosaccharomyces pombe (Cai et al, 2018). In that case, the authors were not able to detect higher-order organization, but instead found that many nucleosomes were partially unwrapped.…”
mentioning
confidence: 99%